2022
DOI: 10.1590/1809-6891v22e-70295
|View full text |Cite
|
Sign up to set email alerts
|

Quality of free-range and commercial eggs subjected to different storage periods and temperatures

Abstract: The objective was to evaluate the internal quality of eggs from commercial laying hens and free-range hens subjected to different storage periods and temperatures. For the experiment, 280 eggs were randomly distributed into different treatments, adopting a completely randomized design, in a 2 x 7 factorial arrangement of two temperatures, seven storage periods, totaling 14 treatments with 10 replications. The treatments consisted of two storage conditions: under refrigeration (6 ± 1.0ºC) and at room temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Furthermore, a notable difference (p<0.05) was observed in yolk color between retail outlets, with supermarket eggs displaying more intense yolk hues than those from street markets (Table 4). The deeper yolk color could suggest a more diverse diet typical of free-range systems, or the inclusion of natural or synthetic colorants, potentially indicating a higher level of carotenoids antioxidants and precursors of vitamin A (Carvalho et al, 2022). Consumers should exercise caution, as there exists a common misconception that brown/red-shelled eggs sold at open markets originate from free-range poultry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a notable difference (p<0.05) was observed in yolk color between retail outlets, with supermarket eggs displaying more intense yolk hues than those from street markets (Table 4). The deeper yolk color could suggest a more diverse diet typical of free-range systems, or the inclusion of natural or synthetic colorants, potentially indicating a higher level of carotenoids antioxidants and precursors of vitamin A (Carvalho et al, 2022). Consumers should exercise caution, as there exists a common misconception that brown/red-shelled eggs sold at open markets originate from free-range poultry.…”
Section: Resultsmentioning
confidence: 99%
“…While the degradation process is inevitable, storage conditions, particularly refrigeration, play a critical role in slowing this decline and ensuring the safety of the product for consumers. As pointed out by Carvalho et al (2022), the current legislation is non-specific for free-range eggs, relying instead on standards set for commercial eggs. This highlights the need for research into the quality of eggs from alternative farming systems, given the limited Brazilian literature on the differences between free-range eggs sold in open-air markets and supermarkets.…”
Section: Introductionmentioning
confidence: 99%
“…These levels differ from those found by Medeiros et al (2022), who found values equal to 12% of the egg size. However, (Carvalho et al, 2022) also found that the average percentage of bark was The difference in the percentage of the shell may be related to the storage method and the nutritional management of laying hens. It was also observed that free-range eggs had lower percentages when compared to commercial eggs.…”
Section: Internal and External Quality Of Eggsmentioning
confidence: 99%
“…Eggs with poor-quality shells are undesirable mainly because they are considered the first protective barrier against the entry of microorganisms into the eggs (Mertens et al, 2006;Janczak & Riber, 2015;Carvalho et al, 2022). The egg is exposed to a series of factors that compromise the microbiological quality, ranging from employees, equipment, facilities, and management to the bird itself (Sharma et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Eggshell is the main factor in maintaining egg quality (Carrillo et al, 2021). Good shell quality will be able to maintain the quality of the eggs, especially the contents of the eggs (Carvalho et al, 2023). According to Jusuf et al (2021), the standard for consumption of chicken eggs based on the level of physical quality of eggs is the condition of the shell, smooth, intact and clean.…”
Section: Introductionmentioning
confidence: 99%